2017
DOI: 10.1159/000484296
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus α-Toxin Induces Inflammatory Cytokines via Lysosomal Acid Sphingomyelinase and Ceramides

Abstract: Background/Aims: Staphylococcus aureus (S. aureus) infections are a major clinical problem and range from mild skin and soft-tissue infections to severe and even lethal infections such as pneumonia, endocarditis, sepsis, osteomyelitis, and toxic shock syndrome. Toxins that are released from S. aureus mediate many of these effects. Here, we aimed to identify molecular mechanisms how α-toxin, a major S. aureus toxin, induces inflammation. Methods: Macrophages were isolated from the bone marrow of wildtype and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…In patients with atopic dermatitis, S. aureus recognition mediated an increase in the production of inflammatory cytokines IL-1β or IFN-γ and promoted the cytokine-dependent growth enhancement of S. aureus, increasing the severity of the skin lesion (33). A recent study suggested that S. aureus-alpha toxin may activate the inflammasome through activation of the acid sphingomyelinase, which resulted in the rapid release of cathepsins and the production of IL-1β and TNF-α in BMdMs (34). The present study demonstrated that S. aureus infection of macrophages triggered a robust increase in the transcriptional expression levels of proinflammatory genes, which was associated with increased expression levels of M1 marker genes.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with atopic dermatitis, S. aureus recognition mediated an increase in the production of inflammatory cytokines IL-1β or IFN-γ and promoted the cytokine-dependent growth enhancement of S. aureus, increasing the severity of the skin lesion (33). A recent study suggested that S. aureus-alpha toxin may activate the inflammasome through activation of the acid sphingomyelinase, which resulted in the rapid release of cathepsins and the production of IL-1β and TNF-α in BMdMs (34). The present study demonstrated that S. aureus infection of macrophages triggered a robust increase in the transcriptional expression levels of proinflammatory genes, which was associated with increased expression levels of M1 marker genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a further study investigated the role of ASM in inflammasome signaling (Ma et al, 2017). Staphylococcus aureus alpha-toxin (α-toxin) is a pore-forming toxin that triggers membrane permeabilization and induces inflammation (Cohen et al, 2016).…”
Section: Asm Links Pamps With the Inflammasomementioning
confidence: 99%
“…Release of cathepsins caused by lysosomal rupture is crucial for inflammasome activation (Hornung et al, 2008;Liu et al, 2016). The pharmacological inhibitor CA-074Me prevents the inflammasome signaling activating and the IL-1β production upon exposure to α-toxin (Ma et al, 2017). Besides, the mature form of cathepsin D follows the ceramide production pattern (Spengler et al, 2018).…”
Section: Asm Links Pamps With the Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…We next determined the nature of SaCPs, as reports suggest that some S. aureus strains survive in acidic compartments containing active lysosomal enzymes (15,17,23). S. aureus-infected hAMs were investigated using fluorescence microscopy to determine bacterial association with the lysosomal aspartyl protease cathepsin D, the most definitive marker of a degradative lysosome.…”
Section: Resultsmentioning
confidence: 99%